Influence of speed fluctuation on cepstrum. (15th March 2019) - Bonnardot, F.
Highlights: Impact of speed fluctuation on cepstrum is studied. A time quefrency representation is used for non-stationary signal analysis. Synthetic signals are used to explain theoretical results. This time quefrency representation is used on Surveillance 8 contest data. Abstract: This paper deals with the influence of speed fluctuations (non-stationary signal) on the cepstrum. After presenting the cepstrum classic properties, the cepstrum of multiple echoes with a period shift is computed. Examples help to interpret the form of the cepstrum. These shifts could be located in the cepstrum as peaks. Next, a discussion about quefrency resolution is made. It is shown that a low quefrency resolution could produce a fusion of cepstrum peaks (positive and negative). In order to take account of speed evolution of the signal a time-quefrency representation is proposed. Synthetic signal is used to show how to interpret this representation. Finally, illustrations on time quefrency representation were made by using gear signals by SAFRAN from the Surveillance 8 contest.